Desafios sociais na educação superior: uma análise dos obstáculos à inclusão de alunas indígenas na UFOPA e o papel das políticas públicas - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This study analyzes the challenges faced by indigenous students at the Federal University of Western Pará (UFOPA) in relation to their inclusion in higher education, investigating the role of public policies in this context. Adopting a mixed approach, the research combines qualitative and quantitative methods to obtain a detailed understanding of the experiences of these students. The sample includes students from several UFOPA courses and institutes, selected by intentional sampling. The data were collected through online questionnaires and content analysis. The study aims to identify the main obstacles, explore academic experiences and promote awareness about the importance of the inclusion of indigenous students in higher education. At the end of the study, we conclude that it is not enough policies to expand the entry of indigenous students, without thinking about their academic path, with policies of effective permanence, in addition to a new model of course structure that values indigenous ancestral knowledge.
Keywords: inclusão; alunas indígenas; educação superior; políticas públicas; CNPQ:: CIÊNCIAS HUMANAS